Inflammatory cytokine upd3 induces axon length–dependent synapse removal by glia - Tenedini, Federico Marcello; Yin, Chang; Huang, Jessica M.; Dhiman, Neena; Soba, Peter; Parrish, Jay Z. (Proceedings of the National Academy of Sciences of the United States of America, 2025)
Many neurodegenerative disorders (NDDs) preferentially affect neurons with long or complex axonal arbors but the cellular and molecular bases for neurite length-dependent vulnerability of neurons to degeneration is largely unknown. Using Drosophila sensory neurons as a model system we show that neuronal activation of the integrated stress response triggers expression of the Interleukin-6 homolog unpaired 3 (upd3), which is both necessary and sufficient for axon length–dependent degeneration of presynapses. Upd3 activates phagocytic glia, triggering phagocytic removal of presynapses preferentially on neurons with long axons, thus revealing an intrinsic axon length–dependent vulnerability to glial insult. Finally, we found that axon length–dependent presynapse loss in fly models of human NDDs utilized this pathway, requiring upd3 and glial expression of the phagocytic receptor draper. Our studies identify inflammatory cytokine signaling and glial phagocytosis as key determinants of axon length–dependent vulnerability, thus mechanistically linking these hallmarks of NDDs.
CRIS-Team Scopus Importer:2025-06-06
Keywords: axon; cytokine; glia; neurodegeneration; neuron

Neural circuits underlying context-dependent competition between defensive actions in Drosophila larvae - Lehman, Maxime; Barré, Chloé; Hasan, Md Amit; Flament, Benjamin; Autran, Sandra; Dhiman, Neena; Soba, Peter; Masson, Jean Baptiste; Jovanic, Tihana (Nature Communications, 2025)
To ensure their survival, animals must be able to respond adaptively to threats within their environment. However, the precise neural circuit mechanisms that underlie flexible defensive behaviors remain poorly understood. Using neuronal manipulations, machine learning-based behavioral detection, electron microscopy (EM) connectomics and calcium imaging in Drosophila larvae, we map second-order interneurons that are differentially involved in the competition between defensive actions in response to competing aversive cues. We find that mechanosensory stimulation inhibits escape behaviors in favor of startle behaviors by influencing the activity of escape-promoting second-order interneurons. Stronger activation of those neurons inhibits startle-like behaviors. This suggests that competition between startle and escape behaviors occurs at the level of second-order interneurons. Finally, we identify a pair of descending neurons that promote startle behaviors and could modulate the escape sequence. Taken together, these results characterize the pathways involved in startle and escape competition, which is modulated by the sensory context.
CRIS-Team Scopus Importer:2025-02-17